1996
DOI: 10.1002/(sici)1098-2264(199606)16:2<138::aid-gcc8>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Frequent loss of heterozygosity for markers on chromosome arm 10q in chondrosarcomas

Abstract: Many tumors exhibit loss of heterozygosity (LOH) for polymorphic markers in regions of the genome that contain genes whose normal function can suppress tumor growth. Mapping of regions of LOH can help identify putative tumor suppressor loci that play a role in the pathogenesis of a disease. We evaluated 18 chondrosarcomas for LOH at 17 short tandem‐repeat polymorphism loci on chromosome 10. Sixty‐seven percent of the tumors (12/18) showed LOH for at least one marker and in most of these tumors the region of lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…More recently Frayling et al 13 using a more centromeric marker (D10S220) showed frequent LOH (37%) in sporadic colorectal adenocarcinomas on 10q11-21 suggesting the presence of a tumour suppressor gene (TSG) in this region. The presence of a TSG in this region is supported by findings in other tumour types including renal, 14 chondrosarcomas 15 and malignant glioma 3 that have shown frequent LOH at 10q11-21.…”
supporting
confidence: 52%
“…More recently Frayling et al 13 using a more centromeric marker (D10S220) showed frequent LOH (37%) in sporadic colorectal adenocarcinomas on 10q11-21 suggesting the presence of a tumour suppressor gene (TSG) in this region. The presence of a TSG in this region is supported by findings in other tumour types including renal, 14 chondrosarcomas 15 and malignant glioma 3 that have shown frequent LOH at 10q11-21.…”
supporting
confidence: 52%
“…56 Chromosome 10 frequently demonstrates LOH in chondrosarcoma, especially at 10q11.2. 57 On the other hand the presence of two copies of certain chromosomes may be essential for growth of transformed cells. In the 29 near-haploid solid tumors retrieved from the literature, chromosome 7 is present in disomic state in 67% of near-haploid solid tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent LOH on chromosome 10 has been reported in a variety of cancers, including glioma, glioblastoma multiforme, prostate cancer, endometrial cancer, chondrosarcoma, bladder cancer, malignant melanoma, and follicular thyroid tumors (Knowles et al, 1994;Gray et al, 1995;Fults and Pedone, 1993;Ittmann, 1996;Trybus et al, 1996;Lacombe et al, 1996;Rasheed et al, 1995;Raskind et al, 1996;Nagase et al, 1996;Zedenius et al, 1996;Isshiki et al, 1993). A limited number of studies have indicated the potential involvement of chromosome 10 in bladder cancer (Knowles et al, 1994;Kallioniemi et al, 1995;Wang et al, 1994).…”
Section: Discussionmentioning
confidence: 99%